Volume 6: Ceramics and Ceramic Composites; Coal, Biomass, Hydrogen, and Alternative Fuels; Microturbines, Turbochargers, and Sm 2021
DOI: 10.1115/gt2021-58960
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Dynamic Behavior of a Single Shaft Gas Turbine Using NARX Models

Abstract: Gas turbines are internal combustion engines widely used in industry as main source of power for aircrafts, turbo-generators, turbo-pumps and turbo-compressors. Modelling these engines can help to improve their design and manufacturing processes, as well as to facilitate their operability and maintenance. These eventually lead to manufacturing of gas turbines with lower costs and higher efficiency at the same time. The models may also be employed to unfold nonlinear dynamics of these systems. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Fuel consumption decreases and a value of about 80% of the optimally achievable fuel savings can be reached by the NARX approach. Hamid Asgari et al [22] reported the ability of open-loop and closed-loop NARX models to predict the dynamic behavior of a single-shaft gas turbine over different operational ranges. Salehi et al [23] showed the effectiveness of a NARX structure to model a fuel flow control system of a turboshaft gas turbine engine.…”
Section: Introductionmentioning
confidence: 99%
“…Fuel consumption decreases and a value of about 80% of the optimally achievable fuel savings can be reached by the NARX approach. Hamid Asgari et al [22] reported the ability of open-loop and closed-loop NARX models to predict the dynamic behavior of a single-shaft gas turbine over different operational ranges. Salehi et al [23] showed the effectiveness of a NARX structure to model a fuel flow control system of a turboshaft gas turbine engine.…”
Section: Introductionmentioning
confidence: 99%